The idea of eco-development in Stefan Kozłowski's works - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2010)
There is a specific way of approaching sustainable development issues in S. Kozłowski’s works. He takes into account a wide spectrum of problems from political, social, economic ones to moral and ethical with reference to the natural environment (ecodevelopment). Frequently, he refers to systemic approaches e.g. researches on harmonized development pointing out the need for using such a perspective. In the researches on sustainable development, there are models including social, technical, and ecological systems. The models take into account a human factor, environment, techniques as well as energy and information. As there is a need for including long term actions related to environmental protection as well as economic mechanisms to carry out sustainable development plans, a new tool emerged called ecological control. Professor Stefan Kozłowski’s approach towards sustainable development including relations between a human and nature accentuates the meaning of quality and the need for natural environmental protection in a process of civilization development of a global society. In his works “eco-development” is used interchangeably with “sustainable development”. Therefore according to S. Kozłowski, the idea of sustainable development cannot be realized in isolation from ecological issues.